Development and progression of microalbuminuria in a clinic sample of patients with insulin dependent diabetes mellitus. Issue 6 (1st June 1998) - Jones, C A; Leese, G P; Kerr, S; Bestwick, K; Isherwood, D I; Vora, J P; Hughes, D A; Smith, C
Abstract : The evolution of abnormal albumin excretion and its association with suggested risk factors were studied in 233 children with insulin dependent diabetes mellitus (IDDM) attending a single paediatric diabetic clinic over an eight year period. Yearly albumin:creatinine ratios (ACR; measured in mg/mmol) in early morning urine samples, glycated haemoglobin (HbA1c), and blood pressure were recorded. Thirty four (14.5%) children had a persistently raised ACR (ACR ⩾ 2.5 mg/mmol on at least three consecutive occasions) and 21 (9%) had an intermittently raised ACR (ACR ⩾ 2.5 mg/mmol on at least two occasions). Factors associated with a persistently raised ACR compared with normal albuminuria in IDDM included longer duration of diabetes, raised median HbA1c during the first five years after diagnosis, and final age adjusted systolic and diastolic blood pressure represented as standard deviation scores. The onset of persistently raised ACR in 13 of 34 children was before puberty and in 23 of 34 children it was within the first four years of diagnosis. The cross sectional prevalence of raised ACR was 12.9% at one year, 18.3% at five years, and 33% at 10 years after diagnosis. Raised ACR occurs frequently before puberty and in the early stages of childhood diabetes.